Analisis Pajak Pertambahan Nilai (PPN) Atas Subsidi Liquedfied Petrolium Gas (LPG) Berdasarkan PMK Nomor 220 Tahun 2020 Pada Agen LPG Di Kabupaten Jember - Della Norma Sakinah; Diana Dwi Astuti; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2023)
This study aims to analyze related facts or phenomena regarding the application of Value Added Tax (VAT) on Liquified Petrol Gas (LPG) subsidies in accordance with the new regulations, namely PMK 03 Number 220 of 2020 for 3 kg LPG Agents in Jember Regency. The population in this study were 23 agents, from 23 research agents taking samples of the object to be studied, namely PT. Surya Perkasa Jaya and PT. Ayu Earth for Business. This type of research method is qualitative with a descriptive approach method. The results of the interviews and analysis stated that PT. Surya Perkasa Jaya has been registered as a Taxable Entrepreneur and has implemented taxation in accordance with existing regulations, namely PMK 220 of 2020 and Law no. 49 of 2009 while at PT. Bumi Ayu Guna Usaha is still not registered as a PKP, so it has not implemented taxation in accordance with its obligations. As a company, it should pay more attention to its obligations, so that it can support the government in equitable distribution of economic growth and national stability.